On transcendental entire solution of Fermat-type trinomial and binomial equations under restricted hyper-order - Banerjee, Abhijit; Sarkar, Jhuma (Annales Mathematicae Silesianae, 2023)
In this paper we are focusing on finding the transcendental entire solution of Fermat-type trinomial and binomial equations, by restricting the hyper-order to be less than one. As the hyper-order is a crucial parameter that characterizes the growth of entire functions, it will be interesting to investigate this unexplored domain, as far as practible, with certain restriction on hyper order. Our results are the improvements of previous results reported in recent papers [12], [13]. We have provided a series of examples to demonstrate and validate the effectiveness of our proposed solutions.